Evaluation of the effectiveness of newly designed motor-driven fiberglass burs versus hand instrumentation in open root planing (Mustansiria Dental Journal, 2018)
The present study was performed to evaluate the effectiveness of newly designedmotor-driven fiberglass burs in root planing and compare it to manual instrumentationusing universal curette. Twelve patients complaining from periodontitis with deepperiodontal pockets were involved in this study. A total number of 139 pocket sitesreceived root planing by motor-driven fiberglass burs and 131 pocket sites wereplaned manually by curette.The root planing procedure was opened type; it was performed by modifiedwidman flap operation. The clinical parameters that were used in this study are(plaque index, bleeding on probing, probing pocket depth and relative attachmentlevel). They were recorded in 4 periodic visits 2 of them before treatment and 2 aftertreatment to assess the improvement and to make a comparison between the twomethods of treatment.The results revealed that there was a significant improvement in all of the clinicalparameters after treatment with fiberglass burs.Also the results showed that that there was no significant difference between theimprovement that was implemented by the two methods of treatment.